Posterior fossa midline mass lesions clinicopathological study and management (Panacea Journal of Medical Sciences, 2022)
Introduction: Some of the most severe brain cancers are tumors in the posterior fossa. This is due to the small space available in the posterior fossa, as well as the possibility of essential brainstem nuclei involvement.Aims: To assess the clinicopathological trends of posterior fossa midline mass lesions and to assess the outcome of the patients following surgery.Materials and Methods: This is a prospective study done in the patients admitted with posterior cranial fossa midline mass lesions who underwent surgical treatment in department of Neurosurgery. Patients were evaluated with regard Age, Sex, Clinical, Radiological and Pathological status at presentation, admission, during and after treatment.Results: Incidence rate of midline mass lesions in posterior fossa is 34.6%. Common age group of occurrence of posterior midline lesions is less than 10 years. Posterior fossa midline lesions are more common in males. The common sites of origin of posterior fossa midline lesions are the Vermis of Cerebellum and fourth ventricle. Most common pathological types are Medulloblastoma and Pilocytic astrocytoma. About 29.6% of posterior fossa midline lesions require CSF diversion prior to definitive surgery. Recurrence is noted in two cases one in brainstem astrocytoma and another in medulloblastoma. Mortality is noted in 18.5% cases of posterior fossa midline mass lesions.Conclusion: Prognosis is good in patients with total excision. This drives the surgeon to go for total excision.